Peran Komunikasi yang Efektif dalam Membangun Keharmonisan Pernikahan - Bunga Surya Azzahra; Herlita Azzahra; Masythah Fauziah Rahmah; Rahmi Ramadhani; Yola Agnesentia; Nurva Dillatul Vatin (Institut Agama Islam Sumatera Barat, 2024)
Effective communication has an important role in building marital harmony. In the context of a husband and wife relationship, open, honest communication and listening to each other can create stronger emotional bonds, reduce conflict and increase satisfaction in marriage. On the other hand, a lack of effective communication can cause misunderstandings, dissatisfaction and potential breakdown in the relationship. Therefore, developing communication skills such as active listening, speaking assertively, and managing conflict is key in creating and maintaining harmony in marriage. This research aims to highlight the importance of effective communication in maintaining domestic happiness and provide practical recommendations for married couples to improve and improve the quality of their communication in order to achieve sustainable marital harmony.